Family farming and its demands. Case study in Oberá (Misiones, Argentina), 2008-2015 - Fernández, Lisandro (2020)
This article identifies and analyses the characteristics of family farm organizations demands of Oberá (Misiones, Argentina), regarding of State intervention on the yerbatero sector, during the period 2008-2015. The interest to study said time lapse is justified in that although there are investigations about the previous and after it, little is known about what happened between 2008 and 2015. In particular, here it is inquired about the object of demands focus on the State role, rather than the methodology of them or the identity of their organizations as they shaped previous studies. The analysis was ordered by two dimensions: the economic-productive and the political-institutional, which allowed to specify the characteristics of the claims and the proposals, and at the same time, provide elements around the agrarian social structure of the territory and the statehood.